Privacidad de la información en la investigación social de naturaleza cualitativa: la transición hacia el mundo digital - Rapimán Salazar, María Eugenia; Chibey Rivas, Tamara Jesús (Acta Bioethica, 2024)
This text addresses the problem of information privacy in qualitative social research developed in the context ofthe digital world. For this purpose, the concept of privacy is reviewed from an analogical view towards its incorporation inthe digital plane with the figure of information privacy and some elements of Gadamer’s hermeneutics. First, the analogicaland ethical plane of privacy is reviewed. Then, the potential of information, the distinction between private and sensitiveinformation and its applicability to social research through the concepts of trust and security are reviewed. Finally, we outlinea proposal for a renewed privacy that proposes to rescue the intersubjectivity that is built in the relationship between theresearch participant and the researcher.